2020
DOI: 10.1126/scitranslmed.aau5732
|View full text |Cite
|
Sign up to set email alerts
|

Prospective longitudinal atrophy in Alzheimer’s disease correlates with the intensity and topography of baseline tau-PET

Abstract: β-Amyloid plaques and tau-containing neurofibrillary tangles are the two neuropathological hallmarks of Alzheimer’s disease (AD) and are thought to play crucial roles in a neurodegenerative cascade leading to dementia. Both lesions can now be visualized in vivo using positron emission tomography (PET) radiotracers, opening new opportunities to study disease mechanisms and improve patients’ diagnostic and prognostic evaluation. In a group of 32 patients at early symptomatic AD stages, we tested whether β-amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
380
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 427 publications
(417 citation statements)
references
References 71 publications
(111 reference statements)
36
380
0
1
Order By: Relevance
“…5,7,19,20 In particular, serum phosphorylated tau (Thr231) is reported to be the most accurate biomarker of TBI severity 17 and is strongly predictive of future neuronal atrophy. 21 While animal models have proven important for modeling TBI and provide a physical and cellular complexity that relatively mimic humans, many pivotal aspects of neurodegeneration are not faithfully recapitulated, such as substantial differences between human and rodent tau protein. 22,23 Previous efforts to study TBI in vitro have used stretch and shear forces to either rodent organotypic slices 24 or rudimentary single-or two-cell type cultures.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,19,20 In particular, serum phosphorylated tau (Thr231) is reported to be the most accurate biomarker of TBI severity 17 and is strongly predictive of future neuronal atrophy. 21 While animal models have proven important for modeling TBI and provide a physical and cellular complexity that relatively mimic humans, many pivotal aspects of neurodegeneration are not faithfully recapitulated, such as substantial differences between human and rodent tau protein. 22,23 Previous efforts to study TBI in vitro have used stretch and shear forces to either rodent organotypic slices 24 or rudimentary single-or two-cell type cultures.…”
Section: Introductionmentioning
confidence: 99%
“…In the first study, beta-amyloid plaques appear to be latecomers to the disease rather than an early trigger in that no statistical difference in plaque load was found during the earliest, subtle cognitive difficulties, suggesting that betaamyloid may not be the trigger for initial disease progression [115]. In the second study, using tau PET imaging (currently under review by the FDA), the authors eloquently demonstrated in early clinical stage AD patients, tau PET brain scans predict the location of brain atrophy measured by MRIs 1-2 years later, but amyloid PET imaging neither predicts the location of either tau nor future atrophy [116].…”
Section: Resultsmentioning
confidence: 99%
“…Microtubule associated protein Tau locates intracellularly and is composed of six isoforms classified into 4-repeat (4R) and 3-repeat (3R) species, and the composition of tau isoforms differ among diverse tauopathies [2]. Tau abnormal accumulation in patients with Alzheimer's disease was found to be closely related to axonal damage, neurodegeneration and cognitive impairment [3][4][5]. This designates tauopathy an important target for early diagnostic and therapeutic intervention for Alzheimer's disease, FTLD, and other tauopathy disorders [6].…”
Section: Introductionmentioning
confidence: 99%